Population and Habitat of the Rainbow Lorikeet (Trichoglossus haematodus) in Leahari Village Forest, Ambon Island - Sahusilawane, John F. (Tropical Small Island Agriculture Management, 2025)
This study aimed to assess the population and habitat characteristics of the Rainbow Lorikeet (Trichoglossus haematodus) in the Leahari Village Forest, Ambon Island. This study was conducted to provide a comprehensive understanding of population density, spatial distribution, and habitat characteristics that support the existence of this species. Direct field observations were conducted using line transect and point count methods, complemented by vegetation analyses to identify food tree species, canopy structure, and other environmental factors influencing the occurence of the Rainbow Lorikeet. The results showed that the Rainbow Lorikeet population in the Leahari Village Forest remains relatively stable, with higher average density observed in primary forest areas compared to secondary forest. The species distribution was concentrated in areas with abundant food trees such as Ficus, Syzygium, and Erythrina, as well as in habitats characterized by dense canopy cover and moderate elevations between 50–200 meters above sea level. Anthropogenic disturbance including land clearing and hunting, were found to negatively affect population numbers, particularly in the forest edge areas. These findings suggest that the persitence of the Rainbow Lorikeet is strongly dependent on the availability of food resources and the sustainability and integrity of its natural habitat. Therefore, conservation strategies should prioritize the protection of key food tree species, the regulation of human activities in and around forest areas, and the enhancement of local community awareness regarding the importance of conserving the Rainbow Lorikeet as part of Maluku's endemic biodiversity.